Examining the Sustainability Report, Financial Performance, and Value of Mining Companies in Indonesia - Dwi Suhartini; Putri, Monika Indah Cahyani; Yunida Putri, Sofie (Yayasan Ilomata, 2024)
This study employs a quantitative approach to explore the intricate interplay among Sustainability Reports, Financial Performance (measured by Return on Assets - ROA), and Firm Value (quantified by Tobin's Q) in Indonesia's dynamic mining industry. Employing purposive sampling, data from 75 samples encompassing 25 mining businesses listed on the Indonesia Stock Exchange (IDX) is examined over the 2020-2022 period. Utilizing statistical analysis, the study employs the Partial Least Squares (PLS) data processing application for partial regression analysis. The findings highlight a substantial and favorable impact of Sustainability Reports on Firm Value, underscoring the growing acknowledgment within Indonesian mining firms of the pivotal role played by both financial and non-financial disclosures. Intriguingly, the study uncovers that Financial Performance, as gauged by ROA, lacks a discernible influence on Firm Value. This nuanced insight suggests a shifting landscape where stakeholders increasingly prioritize comprehensive reporting beyond conventional financial metrics. The research sheds light on the evolving nature of the Indonesian mining sector, emphasizing companies' recognition of the significance of transparent reporting practices. These revelations align with global sustainable development goals, emphasizing the central role played by mining companies in advancing these objectives. In navigating this complex dynamic, the study underscores the crucial role of Sustainability Reports in shaping perceptions and values of mining firms in Indonesia.